Effects of Aluminium on Rice Genotypes under Varying pH Levels in Solution - Soumyasesh Maity; D. Mukhopadhyay; G.C. Banik; B. Roy; M.K. Debnath (Journal of the Indian Society of Soil Science, 2025)
Aluminum (Al) being the third most abundant element in the earth crust, is a main component among numerous minerals in terms of production performances of rice under acidic situation of Sub- Himalayan West Bengal. An attempt was made to study the effects of aluminum under varying pH values on morphophysical parameters of rice.The twenty-one days old rice seedlings were placed in the containers supplied with nutrient solution, where, three pHs (8.0,5.0 and 4.0) were maintained all through out the period of experiments. The rice varieties namely, IR-64 (Al- sensitive) and Uttar Laxmi (Al-tolerant) were considered to assess the effect of Al on the changes of physical parameters of rice. The roots of rice genotypes exhibited distinct and visible symptoms of aluminum toxicity on short term aluminum exposures leading to morphological changes and growth inhibition. The relative root length (RRL) of Uttar Laxmi and IR-64 rice varieties were negatively correlated with Al-concentration. The variations in the dry weight/plant (at 15 and 30 ppm Al-concentrations) for both the varieties were observed at pH 4.0 compared to others. A negative correlation in general between the P-uptake and Al- concentration was observed in rice plants. The Al-resistant variety of rice may be a component under the integrated nutrient management system of rice production in acidic soil. The analysis of the paper can throw light on the possible effect of Al-toxicity on rice genotypes and its management options under acidic situation of sub-Himalayan West Bengal (India).